2016
DOI: 10.1099/mic.0.000325
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite analysis of Mycobacterium species under aerobic and hypoxic conditions reveals common metabolic traits

Abstract: A metabolite profiling approach has been implemented to elucidate metabolic adaptation at set culture conditions in five Mycobacterium species (two fast-and three slow-growing) with the potential to act as model organisms for Mycobacterium tuberculosis (Mtb). Analysis has been performed over designated growth phases and under representative environments (nutrient and oxygen depletion) experienced by Mtb during infection. The procedure was useful in determining a range of metabolites (60-120 compounds) covering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…The characteristic slow growth and the underlying metabolism of NTM enable adaptation to change conditions, turning them less susceptible to antimicrobial agents and disinfectants [ 31 , 69 ] and/or to environmental stresses such as anaerobiosis [ 70 ], starvation [ 71 ], low pH [ 72 ], high temperature [ 73 ], and osmotic stress [ 74 ]. The general adaptation of mycobacteria to extremely stressful conditions is characterized by the entrance of the cell into a dormant state, slowing the metabolism and protecting the cell from life-threatening conditions [ 75 ].…”
Section: Mycobacteria Ecology: the Underlying Resilience Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic slow growth and the underlying metabolism of NTM enable adaptation to change conditions, turning them less susceptible to antimicrobial agents and disinfectants [ 31 , 69 ] and/or to environmental stresses such as anaerobiosis [ 70 ], starvation [ 71 ], low pH [ 72 ], high temperature [ 73 ], and osmotic stress [ 74 ]. The general adaptation of mycobacteria to extremely stressful conditions is characterized by the entrance of the cell into a dormant state, slowing the metabolism and protecting the cell from life-threatening conditions [ 75 ].…”
Section: Mycobacteria Ecology: the Underlying Resilience Biologymentioning
confidence: 99%
“…Additionally, several other genomic mutations, plasmid transfer of resistance determinants, and the production of enzymes that metabolize drugs to a less active form have been described as resistance mechanisms [ 133 , 134 ]. Furthermore, the intracellular growth of NTM [ 10 ] combined with survival in caseum under a non-replicative state of bacterial persistence [ 70 , 135 ], mucus growth [ 135 ], and biofilm growth [ 136 ], make antibiotic delivery and action particularly difficult towards intrinsically resistant NTM [ 137 ]. Although all NTM possess some level of intrinsic resistance to antimicrobials, differences across NTM species have been demonstrated, with, for example, M. kansasii being susceptible to multiple antibiotics, while M. avium is susceptible mainly to macrolides [ 138 ].…”
Section: Mycobacteria Ecology: the Underlying Resilience Biologymentioning
confidence: 99%
“…The culture conditions mimicked by many studies involve a partially aerated or hypoxic NRP state, typically designated on the basis of protocols from Wayne and Hayes [44], which documented an orderly downregulation of the intermediary metabolism, e.g., [27]. Other studies comparing changes of metabolite levels reported a transcriptional mode of regulation under aerated conditions and a more complex metabolic regulation in the presence of hypoxic conditions, e.g., [45]. Despite evident discrepancies about the mode of regulation in previous studies, overall data identified compounds utilised as storage compounds (e.g., succinic acid, triacylglycerides and poly glutamic acid) and arising during the immediate response to resuscitation.…”
Section: Metabolite Profiling a “New” Approach For Drug Discoverymentioning
confidence: 99%
“…Despite evident discrepancies about the mode of regulation in previous studies, overall data identified compounds utilised as storage compounds (e.g., succinic acid, triacylglycerides and poly glutamic acid) and arising during the immediate response to resuscitation. Most of these compounds accumulate intracellularly, but some are transported outside the cell, to reduce toxicity and resulting cellular dysfunction [45,46,47]. The process of resuscitation, which can occur quite suddenly [39], is still poorly understood, as it is difficult to establish the exogenous factors influencing this process [7].…”
Section: Metabolite Profiling a “New” Approach For Drug Discoverymentioning
confidence: 99%
See 1 more Smart Citation